Mapping Ultima Thule Representations of North Greenland in the Expedition Accounts of Knud Rasmussen - Lubowicka, Agata (Studien zur Germanistik, Skandinavistik und Uebersetzungskultur, 2020)
The book addresses the relationship between the literary representations of North Greenland and the Inughuit people in Knud Rasmussen's expedition accounts The New People and My Travel Diary and the historical process of Danish colonization of North Greenland. The aim of reading both works is to demonstrate the ambivalence in representing North Greenland and the Inughuit, and, through this, to prove the existence of common mechanisms and cultural practices connected to mapping of the Other in a situation of asymmetric power relations. Applying a textual approach founded on colonial discourse analysis, the reading proves that literary mappings of geography and identity can never be stable, as they are in the state of constant transformation, perpetually recontextualized and reinvented.